A data mining approach in opponent modeling - Bulos, Remedios De Dios (Animo Repository, 2005)
In offline opponent modeling, large datasets can be utilized as training data to model the opponent. In the Coach competition of RoboCup Soccer, offline opponent modeling can be adopted to train the coach learn about the opponent's behavior patterns. Data-mining techniques, particularly decision-tree construction can be applied in identifying interesting behavior patterns of the opponent. This research explores the use of the decision-tree algorithm C4.5 to generate classification rules that will embody the offensive and defensive strategies (plans) of the coach against its opponent(s). To achieve this objective, the SimSoccer Coach system is built. © Springer-Verlag Berlin Heidelberg 2005.